Systematic Risk in Emerging Markets: a High-Frequency Approach - Arief, Usman (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
The study investigates how systematic, continuous, and discrete (jump) risk can explain the equity returns in Southeast Asia markets. Using the latest econometric techniques and a high-frequency dataset, I construct two high-frequency betas associated with intraday continuous and discontinuous risk premia. To improve consistency, I employ several statistical robustness levels and multiple frequencies (one minutes, five minutes, ten minutes, and thirty minutes). The findings show that both continuous and discontinuous risk premia are significant and positive in Indonesia, and these results are consistent for lower frequency data samples. Furthermore, the study reveals that diffusive and jump risk premia have different impacts in other countries, but the results are not consistent for lower frequency samples.